2022
DOI: 10.7717/peerj.13088
|View full text |Cite
|
Sign up to set email alerts
|

Distinct metabolic profiling is correlated with bisexual flowers formation resulting from exogenous ethephon induction in melon (Cucumis melo L.)

Abstract: Melon (Cucumis melo L.) is an agronomically important vegetable. Most cultivars of melon are andromonoecious and bisexual flowers only emerged from the leaf axil of lateral branches. However, the regulatory mechanism contributing to the occurrence of bisexual flowers were still obscure. In this study, ethephon was applied in two common cultivars of melon. In control without ethephon treatment, no bisexual flower was made in the main stem. However, 6.56 ± 1.42 and 6.63 ± 0.55 bisexual flowers were respectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…(2009) reported that the expression of WIP1 (wound inducible protein1) led to carpel abortion, resulting in the development of unisexual male flowers, and found that ACS‐7 and WIP1 interact to control the development of male, female, and hermaphrodite flowers in melon. Sex determination in melon is mainly controlled by the andromonoecious gene CmACS‐7 (Adnane et al., 2008), the gynoecious gene CmWIP1 (Antoine et al., 2009), and the androecious gene CmACS11 (Fang et al., 2022). CmACS‐7 is a andromonoecious gene that is expressed mainly in the carpel primordia of female and hermaphroditic flowers but does not accumulate in male flowers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2009) reported that the expression of WIP1 (wound inducible protein1) led to carpel abortion, resulting in the development of unisexual male flowers, and found that ACS‐7 and WIP1 interact to control the development of male, female, and hermaphrodite flowers in melon. Sex determination in melon is mainly controlled by the andromonoecious gene CmACS‐7 (Adnane et al., 2008), the gynoecious gene CmWIP1 (Antoine et al., 2009), and the androecious gene CmACS11 (Fang et al., 2022). CmACS‐7 is a andromonoecious gene that is expressed mainly in the carpel primordia of female and hermaphroditic flowers but does not accumulate in male flowers.…”
Section: Introductionmentioning
confidence: 99%
“…CmACS‐7 is a andromonoecious gene that is expressed mainly in the carpel primordia of female and hermaphroditic flowers but does not accumulate in male flowers. It plays an important role in the prevention of stamen development in female flowers (Fang et al., 2022). In addition, CmACS11 is also strongly expressed in the phloem of female and hermaphroditic, but not male, buds and is required for carpel development.…”
Section: Introductionmentioning
confidence: 99%